(3JYdjb Ydi HQOI GdeOjMs - (3eMeO Hf CMeO Hf eMeO Hf EHQGgje GdeMdj GdTGaYj , LdGd GdOjf,J (B864 (3g` s ((3EHQGgje Hf eMeO GdCfOdSi s)
(3ChdgG (B:s
(3bGd GdTjN GdCeGe gPG JYdjb dWja edjM Ydi HQOI GdeOjM , jage Hg ebGUO fGXegG QMeg Gddg hQVi Yfg hbO LQO ef faSg faSG NGWHgG (B:\:" (3Cef JPcQ LjQGf (B" (3HcSQ GdLje s
(3BNQgG (B:s
(3jbhd GLYd GdHQOI Ydi Yjfjc Jfab aMWgG hLYdgG Ydi Yjfjg hbQFJ Ydjg aYhai dhbJg Gddg CYde bGd GdeDda QMeg Gddg Je GdcJGH GdeHGQc SfI CQHY hCQHYjf hKeGf eGFI hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: 27s
(3GdHWGbI GdeUhQI eY GdcJGHRgQ GdYQjT ai CMcGe GdMTjT dHOQ GdOjf GdRQcTi hgh NWCs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs